Potential applications of deep eutectic solvents in nanotechnology - Abo-Hamad, A.; Hayyan, M.; AlSaadi, M.A.; Hashim, M.A. (Elsevier, 2015)
Deep eutectic solvents (DESs) have recently received a great interest in diverse fields including nanotechnology due to their unique properties as new green solvents, efficient dispersants and as large-scale media for chemical and electrochemical synthesis of advanced functional nanomaterials. DESs have also an active role in improving the size and morphology of nanomaterials during synthesis stage. Moreover, DESs confined in nano-size pores or tubes show distinct behavior from those in the same types but in larger scales. Therefore, a numerous studies sprung up to expose the importance of the synergy between DESs and nanomaterials. This review revealed the recent studies that devoted to the impact of involving DESs in nanotechnology and potential applications. (C) 2015 Elsevier B.V. All rights reserved.